The Food Safety Modernization Act and the FDA Facility Registration Program - Susanna Richardson; Renée M. Goodrich-Schneider; Mark A. Ritenour; Michelle D. Danyluk; Keith R. Schneider (EDIS, 2013)
The Food Safety Modernization Act that President Obama signed into law January 4, 2011 represents the most sweeping update to food safety regulation since the Federal Food, Drug, and Cosmetic Act of 1938. As part of FSMA, registration is required of facilities that manufacture, process, pack or hold food for human or animal consumption. This 3-page fact sheet was written by Susanna Richardson, Renée Goodrich Schneider, Mark A. Ritenour, Michelle D. Danyluk, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, July 2013.